Comparison of various methodological approaches to model asbestos thresholds for mesothelioma - Goodman, Julie E.; Korchevskiy, Andrey; Wylie, Ann G. (Frontiers in Public Health, 2025)
BackgroundThere is evidence to support several modes of action (MoAs), and particularly non-genotoxic MoAs, for mesothelioma induced by asbestiform elongate mineral particles (EMPs). In turn, these MoAs provide biological support for dose-response relationships that are non-linear and that include a threshold. However, statistical models of human data have not adequately addressed threshold dose-response relationships for asbestiform EMPs and mesothelioma. In addition, unlike other carcinogens, asbestiform EMPs are not uniform materials and display a range of properties.ObjectivesOur objective was to review various approaches for applying threshold dose-response models to asbestiform EMPs and mesothelioma.Materials and methodsWe collected data from several sources, including the Surveillance, Epidemiology, and End Results (SEER) Program and published case-control studies, cohort studies, and a meta-analysis that evaluated various mineral types of asbestos and mesothelioma risk. Several threshold-based models were fit to the available data. We also evaluated thresholds for certain fiber characteristics.ResultsCertain characteristics of asbestiform EMPs, such as width, length, and surface area, likely have thresholds for mesothelioma. Theoretical models and models based on epidemiology data supported thresholds. A Monte Carlo evaluation of the threshold hypothesis for mesothelioma in a meta-analysis of occupational exposures to various mineral fiber types, using a cumulative exposure metric, demonstrated the likelihood of a threshold to be 72% for non-textile chrysotile, 80.9% for textile chrysotile, 84% for amosite, and 60% for crocidolite. A multi-stage clonal expansion (MSCE) model applied to the SEER mesothelioma registry data demonstrated a good fit with the inclusion of a threshold by a surrogate predictor of cumulative exposure to amphiboles. Finally, lung burden studies also support a threshold. Our preliminary estimate of a central-tendency cumulative exposure threshold level for non-textile chrysotile is ~90 f/cc-years. Based on our proposed approach, we suggest thresholds of 1.04 f/cc-years for amosite, 0.25 f/cc-years for crocidolite, and 4.3–10.9 f/cc-years for tremolite. Future studies should be conducted to support these estimates.ConclusionsWhile uncertainties remain, many angles of scientific evidence support the existence of mineral-specific thresholds for mesothelioma.